Changes in global and relationship-specific attachment working models. (October 2022) - Dugan, Keely A.; Fraley, R. Chris; Gillath, Omri; Deboeck, Pascal R.
Attachment theorists suggest that people construct a number of distinct working models throughout life. People develop global working models, which reflect their expectations and beliefs concerning relationships in general, as well as relationship-specific working models of close others—their mothers, fathers, romantic partners, and friends. The present research investigated the interplay of these different working models over time. We analyzed longitudinal data collected from 4, 904 adults (mean age = 35.24 years; SD = 11.63) who completed between 3 and 24 online survey assessments (median test–retest interval = 35 days). Using latent growth curve modeling, we examined the associations among both long-term changes and short-term fluctuations in participants' working models. Our findings suggest that different working models not only change together over the long run, but also exhibit co-occurring, short-term fluctuations. This was true concerning the associations between global and relationship-specific models as well as among different relationship-specific models.